Ulama, State, and Politics in Myanmar - Kadoe, Naw Lily; Husein, Fatimah (Al-Jamiah: Journal of Islamic Studies, 2015)
Issues related to Islam and Myanmar have become worldâs attention, especially in relation to the Rohingya refugees who fled the country in the past few months. The 2010 government census stated that Muslim constitutes 3.9% ofÂ  the total 53 million population, who are mainly Theravada Buddhists; but some Muslim leaders interviewed in September 2014 argued that the followers of Prophet Muhammad constituted 17%. This paper finds that violent conflicts involving Muslims and Buddhists in Rakhine State were caused by complex issues including the historical background ofÂ  the coming and development ofÂ  Islam in Myanmar and the authoritarian military regime, which did not open paths for dialogue. It is surprising to witness how the concept ofÂ  âpeaceâ that is at the heart ofÂ  the Buddhist teaching seems to be disappeared in the whole issue ofÂ  the conflicts. This paper, however, will not focus on the conflicts themselves but on the role ofÂ  ulama during the Myanmar conflict.[Isu terkait Islam dan Myanmar telah menyita perhatian dunia, khususnya setelah adanya para pengungsi Rohingya yang keluar dari negeri ini beberapa bulan yang lalu. Sensus tahun 2010 yang dilakukan pemerintah menunjukkan bahwa penhanut Islam berjumlah 3,9% dari total 53 juta penduduk yang mayoritas penganut Budha Theravada; namun menurut beberapa tokoh Islam yang diwawancarai padaÂ  September 2014, penganut Islam mencapai 17%. Tulisan ini melihat bahwa konflik kekerasan antara Muslim dan Budha di Provinsi Rakhine dilatarbelakangi persoalan yang cukup komplek, termasuk latar sejarah masuk dan berkembangnya Islam di Myanmar serta rezim militer yang otoriter yang tidak pernah membuka ruang dialog. Satu hal yang cukup mengejutkan adalah konsep âdamaiâ yang menjadi jantung ajaran Budha tampaknya hilang di telan pusaran konflik.Hanya saja, tulisan ini tidak berfokus pada isu konflik itu sendiri, namun lebih menelisik peran ulama dalam konflik Myanmar.]